Dictyostelium Dynamin Superfamily GTPases Implicated in Vesicle Trafficking and Host-Pathogen Interactions - Katic, Ana; Hüsler, Dario; Letourneur, François; Hilbi, Hubert (Frontiers in Cell and Developmental Biology, 2021)
The haploid social amoeba Dictyostelium discoideum is a powerful model organism to study vesicle trafficking, motility and migration, cell division, developmental processes, as well as host cell-pathogen interactions. Dynamin superfamily proteins (DSPs) are large GTPases, which promote membrane fission and fusion, as well as membrane-independent cellular processes. Accordingly, DSPs play crucial roles for vesicle biogenesis and transport, organelle homeostasis, cytokinesis and cell-autonomous immunity. Major progress has been made over the last years in elucidating the function and structure of mammalian DSPs. D. discoideum produces at least eight DSPs, which are involved in membrane dynamics and other processes. The function and structure of these large GTPases has not been fully explored, despite the elaborate genetic and cell biological tools available for D. discoideum. In this review, we focus on the current knowledge about mammalian and D. discoideum DSPs with a particular emphasis on the pathogenesis of the facultative intracellular bacterium Legionella pneumophila, and we advocate the use of the genetically tractable amoeba to further study the role of DSPs in cell and infection biology.